Euro-productivity and euro-jobs since the 1960s: which institutions really mattered? - Peter Lindert; Gayle Allard (University of California, Department of Economics, 2006)
How have labor market institutions and welfare-state transfers affected jobs and productivity in Western Europe, relative to industrialized Pacific Rim countries? Many studies have tackled this question, with mixed and often unclear results. This paper proposes an eclectic comparative economic history, giving a clearer answer to the issue than past studies have implied. Orthodox criticisms of European government institutions are right in some cases and wrong in others. Protectionist labor-market policies such as employee protection laws seem to have become more costly since about 1980, not through overall employment effects, but through the net human-capital cost of protecting senior male workers at the expense of women and youth. Product-market regulations in core sectors may also have reduced GDP, though here the evidence is less robust. By contrast, high general tax levels have shed the negative influence they might have had in the 1960s and 1970s. Similarly, other institutions closer to the core of the welfare state have caused no net harm to European jobs and growth. Coordinated collective wage bargaining has saved jobs throughout the postwar period, with no cost in terms of productivity. The welfare state's tax-based social transfers have not harmed either employment or GDP. Even unemployment benefits do not have robustly negative effects.
Keywords: 330; Arbeitsmarkt; Institutionelle Infrastruktur; Soziale Sicherung; Arbeitslosigkeit; Produktivität; Vergleich; EU-Staaten; OECD-Staaten